Absolute quantification of sp3 defects in semiconducting single-wall carbon nanotubes by Raman spectroscopy - Sebastian, Finn; Zorn, Nicolas; Settele, Simon; Lindenthal, Sebastian; Berger, Felix J.; Bendel, Christoph; Li, Han; Flavel, Benjamin S.; Zaumseil, Jana (The journal of physical chemistry letters, 2022)
The functionalization of semiconducting single-wall carbon nanotubes (SWCNTs) with luminescent sp3 defects creates red-shifted emission features in the near-infrared and boosts their photoluminescence quantum yields (PLQYs). While multiple synthetic routes for the selective introduction of sp3 defects have been developed, a convenient metric to precisely quantify the number of defects on a SWCNT lattice is not available. Here, we present a direct and simple quantification protocol based on a linear correlation of the integrated Raman D/G+ signal ratios and defect densities as extracted from PLQY measurements. Corroborated by a statistical analysis of single-nanotube emission spectra at cryogenic temperature, this method enables the quantitative evaluation of sp3 defect densities in (6,5) SWCNTs with an error of ±3 defects per micrometer and the determination of oscillator strengths for different defect types. The developed protocol requires only standard Raman spectroscopy and is independent of the defect configuration, dispersion solvent, and nanotube length.